PROTOCOL: Effectiveness of interventions for improving livelihood outcomes for people with disabilities in low‐ and middle‐income countries: A systematic review - Xanthe Hunt; Ashrita Saran; Lena Morgon Banks; Howard White; Hannah Kuper (Campbell Systematic Reviews, 2021)
Abstract The objectives of this review are to answer the following research questions: (1) What is the effect size of the effectiveness of interventions to improve livelihood outcomes for people with disabilities in low‐ and middle‐income countries (LMICs), and what is the quality of the evidence base? (2) What works to improve livelihood outcomes for people with disabilities in LMICs? (3) Which interventions appear most effective for different categories of disability? (4) What are the barriers and facilitators to the improvement of livelihood outcomes to people with disabilities?